Mendeley Dekstop Training For Improving Elementary School Teacher Competence In SDN 1 Wadunggates Klaten - Meidawati Suswandari; Dwi Anggraeni Siwi; Moefty Mahendra; Sri Mulyati (STKIP Singkawang, 2020)
This study has a goal to improve the competence of elementary school teachers at SD N 1 Wadunggates Klaten through virtual citation training using Mendeley. The methods used in this community service included lecturing, implementation of Mendeley Desktop, practice, assignments, and questions and answers. Then, the partner school was involved to play an active role through various activities and training to be implemented. The training activities carried out in this community service showed that, after the implementation of the Mendeley training, the knowledge of the teachers significantly increased. It appears that most of them have acquired sufficient additional knowledge. Mendeley training can be a supporting means of making good and appropriate scientific references.